Distribution and space autocorrelation of illicit drug cases in a northwest agricultural council (Research, Society and Development, 2020)
The article aims to verify the spatial distribution and autocorrelation of cases of individuals indicted for possession of illicit drugs in a municipality in the northeast of Brazil. This is an exploratory, quantitative, cross-sectional study, based on primary documents, based on those of the Finding Reports pertinent to the Institute of Scientific Police of Paraíba, between the years 2013 and 2017. Maps (Lisa and Moran) were generated for the demonstration of the spatial distribution of the notifications, as well as diagrams, using the Moran Global Index and the Local Moran Index, with the aid of the free statistical software The R Project for Statistical Computing (version 3.4.2). The variable “Neighborhood of occurrence” was adopted as the unit of verification to guide the spatial analysis. The neighborhoods of Serrotão (n = 143), José Pinheiro (n = 102) and Bodocongó (n = 77) constituted the three neighborhoods with the highest number of cases recorded throughout the study period. Significant statistical results were found for the local spatial autocorrelation between the peripheral neighborhoods of Serrotão, Bodocongó, Três Irmãs, Malvinas and José Pinheiro, but in different years. In view of this, the present study permeated the decision-making process in the face of the drug phenomenon, in addition to being a useful tool to guide the planning of actions to combat illegal consumption and commercialization in the northeastern rural region.